Patrick Gray, "Shakespeare and the Fall of the Roman Republic: Selfhood, Stoicism and Civil War", Edinburgh: Edinburgh University Press, 2020 (paperback edition), 320 p. - Gabriela CHEAPTANARU (Studia Universitatis Babeş-Bolyai. Philologia, 2023)
Shakespeare attribute to the fall of the Roman Republic? In his book, Shakespeare and the Fall of the Roman Republic: Selfhood, Stoicism and Civil War, Patrick Gray provides a thought-provoking answer. In his analysis of Julius Caesar and Antony and Cleopatra (and tangentially on Coriolanus as well), Gray advances a daring and illuminating hypothesis. He demonstrates that, for Shakespeare, the Romans’ Stoic denial of “passibility” (8) and their inability to exhibit Christian pity and empathy constitute their chief fatal flaws, which set their tragedy into motion. Thus, the researcher sets the illusory figure of the isolated, self-sufficient Stoic against Shakespeare’s Christian understanding of the self as inevitably vulnerable, and against the assumption that authentic selfhood can only be attained within a community.